Agricultural impacts on lowland tropical streams detected through leaf litter decomposition - Javier Pérez; Luz Boyero; Ana Raquel Tuñón; Brenda Checa; Francisco Correa-Araneda; Alisson Guerra; Anyi Tuñón; Dania Castillo; Edgar Pérez; Gabriela García; Randhy Rodríguez; Aydeé Cornejo (Ecological Indicators, 2023)
Stream ecosystems are highly vulnerable to changes in land use and vegetation in their catchments for two reasons: firstly, they receive inputs of nutrients, contaminants and sediments through runoff; and secondly, terrestrial leaf litter is the major basal resource supporting their food webs. Leaf litter decomposition by microorganisms and detritivores is thus a key stream ecosystem process, and a valuable functional indicator of impacts associated to agriculture and other alterations of human origin. Here, we investigated the joint effects of land use changes associated to agriculture (low, medium and high intervention areas: LI, MI and HI, respectively) in a tropical lowland catchment in Panama, through a decomposition experiment using three leaf litter types differing in nativeness (Ficus insipida, native to the study area; Alnus acuminata, native to Panama but not present in the study area; and Musa balbisiana, exotic to Panama). Lowland tropical areas are often poor in litter-consuming detritivores, and we accordingly observed a high contribution of microorganisms to total decomposition (>60% on average). However, only in the presence of detritivores, decomposition of Alnus discriminated among different degrees of agricultural intervention, being higher at the LI area. Leaf litter of the native Ficus showed higher microbial decomposition than the other types, possibly in relation to a home-field advantage effect. Despite the scarcity of detritivores in tropical lowland streams compared to tropical highland or temperate streams, our study indicates that their activity reflects impacts of land use change on these streams and they should therefore be included in assessments of anthropogenic impacts.